The Association Between Emotional Intelligence and Suicidal Behavior: A Systematic Review - Domínguez-García, Elena; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2018)
Background: Some meta-analyses have demonstrated the association between emotional intelligence (EI) and different health indicators. With the increase of suicide cases in the world, more and more professionals have been interested in the link between both variables. Aim: to study all the available evidence on the association between EI and suicidal behavior. Method: we systematically reviewed all available literature (in English or Spanish) on the relationship between both variables through the main databases. Results: twenty-five articles were included. EI and suicidal behavior correlated inversely in almost all the articles that the Emotional Quotient Inventory (EQ-i), The Emotional Intelligence Test (EIT), The Spanish Wong and Law Emotional Intelligence Scale (WLEIS) and The Schutte Emotional Intelligence Scale (EIS/SSEIT), Barchard’s Emotional Intelligence Scale, were used, that is, the higher suicidal behavior level the lower the EI score. The same results were found in two out of four investigations that used the Trait Meta-Mood Scale (TMMS-24) between clarity (emotional understanding) and emotional repair (emotional regulation) and suicidal behavior. Two out of three studies that used the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) found that only the Strategic component of EI (emotional understanding and regulation) was a protective factor. Conclusions: The results appear to indicate that a high level of EI plays an important role in protecting against suicidal behavior, and should thus be integrated into suicide prevention programs. Keywords: Emotional intelligence, suicide, suicidal behavior, suicide risk, emotional skills, emotional competence, systematic review.